IS THERE ANY PLACE LEFT FOR OMEGA-3 FATTY ACIDS IN CARDIAC SURGERY? - V. V. Lomivorotov; S. M. Efremov; M. N. Abubakirov; Christian Stoppe (Вестник анестезиологии и реаниматологии, 2018)
Goal of the review: to study theoretical and applied aspects of using omega-3 fatty acids in the high risk patients undergoing cardiac surgery in order to reduce the intensity of system inflammatory response, caused by cardiopulmonary bypass and forming the basis of organ dysfunctions in the post-operative period.